USING DEMONSTRATION TECHNIQUE AND COLLABORATIVE WRITING STRATEGY TO TEACH WRITING A PROCEDURE TEXT TO VOCATIONAL HIGH SCHOOL STUDENTS - Ilham Ferdias; Yenni Rozimela (Universitas Negeri Padang, 2017)
Writing is one language skill that the students must master in learning English. Writing a procedure text is included as well. However, some students seem to face several problems in writing the text, such as students’ failure in understanding the text structure and features of a procedure text as well as difficulties in understanding and applying their ideas in writing the text. Therefore, it is necessary to propose and use some technique that can effectively enhance students’ cognitive performance as well as attract their attention during classroom learning activity so that their ability in writing a procedure text improves hopefully. In this circumstance, teachers can use the combination of demonstration technique and collaborative writing strategy. The techniques can help teachers during the learning activities and assist the students in understanding the given lesson. Demonstration technique requires teachers to perform a demonstration of a process or set of steps of certain topics in teaching writing procedure text that can completely attract students’ attention. Meanwhile, collaborative writing strategy can help students understand the procedure text, its social function, the structure and language features of the text as well provide students assistance in composing and writing the text as they work in groups. Thus, by using these techniques, teachers can cope with the difficulties in learning process, and students are expected to successfully manage their problems in understanding the procedure text, its social function, and the structure as well as the language features of the text and to effortlessly apply and use their ideas in writing a procedure text.